CH-π and CF-π interactions lead to structural changes of N-heterocyclic carbene palladium complexes - Xu, Xiangya (2014)
The role of CH–π and CF–π interactions in determining the structure of N-heterocyclic carbene (NHC) palladium complexes were studied using 1H NMR spectroscopy, X-ray crystallography, and DFT calculations. The CH–π interactions led to the formation of the cis-anti isomers in 1-aryl-3-isopropylimidazol-2-ylidene-based [(NHC)2PdX2] complexes, while CF–π interactions led to the exclusive formation of the cis-syn isomer of diiodobis(3-isopropyl-1-pentafluorophenylimidazol-2-ylidene) palladium(II).